Միֆը և իրականությունը Ավետիք Իսահակյանի «ռոտմիստր Վ. Պավլովիչի երազը» պատմվածքում - Մանուկյան, Արմեն Լևոնի (Արմավ հրատ.)
In the original and colorful gallery of heroes, created by the great Armenian poet and prose writer Avetik Isahakyan, a Russian emigrant officer, the main hero of the story “The Dream of Captain V. Pavlovich”, occupies s special place. The former captain of the tsarist, and then the Kolchak army, Vladimir Pavlovich visits the Paris restaurant of his old acquaintance, the former Moscow restaurateur Kuzma Matfeich, to pour out his longing. The action develops through dialogue, and Isahakyan skillfully reveals step by step the folds of the captain’s soul, illuminates the darkest corners of this “mysterious Russian soul”, thereby revealing the tragedy of Russian emigrants. In Vladimir Pavlovich’s long monologues intertwine the past, present and future, myth and reality, and this two play a significant role in all three periods of time, transform into each other or are compared to each other, thereby helping the author to complete what he said. With its cruel truthfulness, the depth of penetration into the soul of a Russian person, a Russian emigrant and artistic qualities, Isahakyan’s story “The Dream of Captain V. Pavlovich” is one of the best examples of Armenian prose and at the same time one of the best works written on this topic in general. It is high time to translate it into Russian and other languages and present it to a foreign reader so that it takes its rightful plase among the well-known works on the theme of Russian emigrants. В своеобразной и красочной галерее героев, созданной великим армянским поэтом и прозаиком Аветиком Исаакяном, свое особое место занимает русский офицер-эмигрант – главный герой рассказа ”Сон ротмистра В. Павловича”. Бывшый ротмистр царской, а потом колчаковской армии Владимир Павлович посещает парижский ресторан своего давнего знакомого, бывшего московского ресторатора Кузьмы Матфеича, чтобы излить свое тоску. Действие развивается через их диалог, и Исаакян искусно шаг за шагом раскрывает складки души ротмистра, освещает самые темные уголки этой «загадочной русской душы», раскрывая тем самым трагедию русских эмигрантов. В длинных монологах Владимира Павловича переплетаются прошлое, настоящее и будущее, миф и реальность, и эти двое играют значительную роль во всех трех периодах времени, трансформируются друг в друга или сопоставляются друг к другу, тем самым помогая автору дополнить сказанное им.Своей жестокой правдивостью, глубиной проникновения в душу русского человека, русского эмигранта и художественными качествами рассказ Исаакяна “Сон ротмистра В. Павловича” – один из лучших образцов армянской прозы и в то же время одно из лучших произведений, написанных на эту тему вообще. Давно пора его перевести на русский и другие языки и представить иноязычному читателю, чтобы он занял свое достойное место среди известных произведений на тему русских эмигрантов.
Keywords: Գրականություն